PENDAMPINGAN PERHITUNGAN BREAK EVEN POINT PADA BUMDES TERUS JAYA PARAGE DESA PARAGE KECAMATAN CIKULUR - Monica Lestari; Rudiyanto; Herlina; Ela Widasari; Siti Mudawanah (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2022)
Break Even Point (BEP) analysis or break even point is an analysis technique carried out to study the relationship between fixed costs, variable costs, expected profit and sales volume in general. This analysis also provides an idea for company management to find out what the minimum sales are in one accounting period so that operational activities do not experience losses. In the mentoring process carried out at BUMDesTeru Jaya Parage tries to provide knowledge about the importance of profit planning and analyzing Break Even Points so that BUMDES can avoid the problem of suffering losses. In this assistance the author also provides an understanding of the steps for calculating BEP as a basis for profit planning. The aim of this activity is to apply the accounting knowledge that the author has gained from learning activities on campus, as well as to help BUMDes Continue Jaya Parage in calculating BEP for the Pom Mini trading business as a basis for profit planning. The result is that BUMDes can calculate BEP properly and correctly and can make profit plans with a profit target of 50%. And during the December 2019 period, BUMDes continued to be successful, surpassing its break-even point.